Knowledge and practice on postnatal care among postnatal mother in Hospital Universiti Sains Malaysia - Anuar, Mardiah Husna Ahmad (2020)
Postnatal period is considered a critical time for all woman after giving birth where now days the range of mortality and morbidity are very high. Every woman will experience different situations during postnatal period and a proper and good care can reduce complication. This study aimed to identify the knowledge and practice regarding postnatal care among postnatal mother in Hospital Universiti Sains Malaysia (USM). A cross-sectional descriptive study was used in this study. Simple random sampling technique was used to select the postnatal mothers. 153 postnatal mother were selected to answer the structured questionnaire. The collected data were analysed by using descriptive statistics (frequency and percentage) and inferential statistics (chi-square). A total of 23 respondents were categorised in poor level, 59 in moderate level and 71 respondents in good level of knowledge. Meanwhile, 31 participants were categorized as having low levels of practice, 111 respondents in satisfactory level and 11 respondents in good level. There is a significant relationship between level of knowledge with practice (p-value 0.028) and parity (p-value 0.037). Finding of the study found out that postnatal mother had good level of knowledge and had satisfactory level of practice. There are association between level of knowledge with level of practice and parity. While there are no association between level of knowledge with age, ethnicity, educational status, employment status, monthly income and source of information. The structure formal educational and mass media content is needed for improving the knowledge and practice of postnatal mother.